1995
DOI: 10.1128/mcb.15.10.5322
|View full text |Cite
|
Sign up to set email alerts
|

A Truncated Herpes Simplex Virus Thymidine Kinase Phosphorylates Thymidine and Nucleoside Analogs and Does Not Cause Sterility in Transgenic Mice

Abstract: Dividing eukaryotic cells expressing the herpes simplex virus type 1 thymidine kinase (TK) gene are sensitive to the cytotoxic effect of nucleoside analogs such as acyclovir or ganciclovir (GCV). Transgenic mice with cell-targeted expression of this conditional toxin have been used to create animals with temporally controlled cell-specific ablation. In these animal models, which allow the study of the physiological importance of a cell type, males are sterile. In this study, we showed that this phenomenon is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 44 publications
2
40
0
Order By: Relevance
“…Among three UCP-TK founder mice, two female mice exhibited germ-line transmission of the transgene whereas a male founder was sterile, consistent with previous reports that transgenic mice harboring the HSV-TK gene produce abnormal sperms due to a testis specific extra transcription initiation site within the HSV-TK gene (Robert et al, 1990;Salomon et al, 1995; see also Figure 1B). The copy number of the transgene was estimated to be approximately 5 by genomic Southern blotting using UCP1 and HSV-TK gene probes and genomic DNA prepared from various tissues from transgenic mice (data not shown).…”
Section: R Esults and Discussion Production Of Transgenic M Ice W Itsupporting
confidence: 76%
“…Among three UCP-TK founder mice, two female mice exhibited germ-line transmission of the transgene whereas a male founder was sterile, consistent with previous reports that transgenic mice harboring the HSV-TK gene produce abnormal sperms due to a testis specific extra transcription initiation site within the HSV-TK gene (Robert et al, 1990;Salomon et al, 1995; see also Figure 1B). The copy number of the transgene was estimated to be approximately 5 by genomic Southern blotting using UCP1 and HSV-TK gene probes and genomic DNA prepared from various tissues from transgenic mice (data not shown).…”
Section: R Esults and Discussion Production Of Transgenic M Ice W Itsupporting
confidence: 76%
“…18 -20 With activation of the "suicide" gene TK, the phosphorylated products of ganciclovir (GCV) 21 are able to deplete the proliferating FSP1 ϩ cells in vivo selectively. In the current study, we showed for the first time that depletion of proliferating fibroblasts during the tumor promotion stage decreased the incidence and number of papillomas as well as their malignant conversion rate.…”
mentioning
confidence: 99%
“…Toxicity due to HSV1 -TK expression has also been seen in the pituitary tumor cell line GH3 35 and in transgenic male mice expressing HSV1 -TK. 42 The second gene therapy approach tested was the RAd delivery of mFasL. Four of the five cell cultures tested were killed by this treatment method.…”
Section: Discussionmentioning
confidence: 99%